ИНФЕКЦИОННЫЙ ЭНДОКАРДИТ ТРАНСПЛАНТИРОВАННОГО СЕРДЦА - НОВОЕ ЛИЦО ИЗВЕСТНОЙ БОЛЕЗНИ - И. И. Резник; Э. М. Идов; А. И. Иофин; А. Н. Быков; Ю. А. Завершинский (SINAPS LLC, 2014)
The first review of endocarditis following solid organ transplantation was published in 1989. At present time infective endocarditis is a known complication of cardiac transplantation. However, published information has been limited. There are practically no materials with a description of infective endocarditis following ortotopic heart transplantation in our literature. The authors of this article describe one case caused by Staphylococcus aureus.